2014
DOI: 10.1038/jid.2014.147
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronan Metabolism in Human Keratinocytes and Atopic Dermatitis Skin Is Driven by a Balance of Hyaluronan Synthases 1 and 3

Abstract: Hyaluronan (HA) is a glycosaminoglycan synthesized directly into the extracellular matrix by three hyaluronan synthases (HAS1, HAS2, and HAS3). HA is abundantly synthesized by keratinocytes but its epidermal functions remain unclear. We used culture models to grow human keratinocytes as autocrine monolayers or as reconstructed human epidermis (RHE) to assess HA synthesis and HAS expression levels during the course of keratinocyte differentiation. In both the models, epidermal differentiation downregulates HAS3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
67
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 62 publications
(73 citation statements)
references
References 44 publications
5
67
0
1
Order By: Relevance
“…2a), in agreement with the upregulation observed in AD. 4,8 Though, no significant changes were found with respect to HAS1 expression levels (data not shown), unlike data collected from AD lesions. S4a).…”
Section: Resultsmentioning
confidence: 60%
“…2a), in agreement with the upregulation observed in AD. 4,8 Though, no significant changes were found with respect to HAS1 expression levels (data not shown), unlike data collected from AD lesions. S4a).…”
Section: Resultsmentioning
confidence: 60%
“…Hyaluronidase Treatment Decreases HA Production without Affecting Cell Proliferation-Previously, we demonstrated that hyaluronidase treatment does not affect the differentiation of keratinocyte monolayer models (16). Here, we investigated the effect of HA degradation on proliferation in the same model.…”
Section: Resultsmentioning
confidence: 95%
“…In those studies, we suppressed HA from keratinocyte monolayer cultures using either 4MU or hyaluronidase. Surprisingly, HA depletion had no influence on the differentiation process (16). In light of those conflicting data, the present study was designed to unravel the role of HA in proliferation and differentiation of human keratinocytes grown in a monolayer model and in an in vitro model that is as close as possible to native human epidermal growth, i.e.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…During spontaneous differentiation of keratinocytes HA of high molecular mass accumulates simultaneously with increased HAS1 and decreased HAS2/3 expressions. (Malaisse et al, 2014). Under physiological conditions HA catabolism is mainly due to hyaluronidases (HYAL).…”
mentioning
confidence: 99%